2022
DOI: 10.1177/23259671211059541
|View full text |Cite
|
Sign up to set email alerts
|

Return to Play and Player Performance After Meniscal Tear Among Elite-Level European Soccer Players: A Matched Cohort Analysis of Injuries From 2006 to 2016

Abstract: Background: Meniscal injuries are extremely common in soccer athletes, and little is known about postrecovery performance. Purpose: To (1) identify characteristics associated with return to play (RTP) to the same league level and (2) evaluate long-term effects that injury and management approach may have on player performance. Study Design: Cohort study; Level of evidence, 3. Methods: Using publicly available records, we identified athletes who sustained meniscal tears across the 5 major European soccer league… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…These findings have great practical implications. When an injury occurs, not only does it bring the athlete's activity to a stop, but it may cause a reduction in muscle tone and functional capacity [26,27], affecting their adaptation and subsequent performance [43][44][45]. It is therefore important to apply techniques that allow a more rapid but also more effective recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings have great practical implications. When an injury occurs, not only does it bring the athlete's activity to a stop, but it may cause a reduction in muscle tone and functional capacity [26,27], affecting their adaptation and subsequent performance [43][44][45]. It is therefore important to apply techniques that allow a more rapid but also more effective recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of muscle mass or small variations in postural aspects may result in less effectiveness in their actions. In addition, this could give rise to a loss of confidence, affecting the athlete's performance [43][44][45][46]. For these reasons, one of the objectives, when athletes are injured, is to try to restore their biomechanical capabilities and musculoskeletal functionality.…”
Section: Introductionmentioning
confidence: 99%
“…14 Meniscal tears can also be debilitating injuries, potentially requiring up to 58 days for RTP in one study, with players often having to return the following season if meniscal surgery is performed. 15 Inadequate or inappropriate training and warm-up, excessive training, and insufficient recovery time between play predispose any athlete to overuse injuries, which account for up to a third of all sports injuries. 16 Overuse tendinopathy is commonly seen involving the supraspinatus, wrist extensors, patellar, quadriceps, and Achilles tendons across a variety of sports (►Fig.…”
Section: Return To Play In the Professional Athletementioning
confidence: 99%
“…14 Meniscal tears can also be debilitating injuries, potentially requiring up to 58 days for RTP in one study, with players often having to return the following season if meniscal surgery is performed. 15…”
Section: Soft Tissue Injuriesmentioning
confidence: 99%
“…3 In addition, meniscal tears tend to occur 6 to 9 times more frequently during competitive soccer matches than routine practice. 4 Lavoie-Gagne et al 5 in their study on RTP after traumatic meniscal tears in elite European soccer players reported that age younger than 30 years, more goals scored preinjury and surgical…”
Section: Introductionmentioning
confidence: 99%